2018
DOI: 10.1002/vnl.21689
|View full text |Cite
|
Sign up to set email alerts
|

Gamma induced changes in the structure and optical properties of ZnS/PVA nanocomposite

Abstract: Nanocomposite of polyvinyl alcohol (PVA) and zinc sulfide (ZnS) was fabricated by ex situ casting technique. ZnS nanoparticles were prepared by chemical coprecipitation method in air atmosphere using EDTA-ethylenediamine as stabilizing agent. Rietveld refinement of X-ray data showed that the prepared ZnS adapts cubic zinc blend structure with a lattice parameter fits 5.345 Å and a mean grain size of 4 nm. Samples from ZnS/PVA nanocomposite have been exposed to gamma doses in the range 0-400 kGy. The effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Δ W values were calculated applying Scherrer equation [ 20 ] : L=()0.89×λ/()W0.25emCos0.25emθ Δ W is the peak's halo's width at half maximum intensity. λ is X‐ray wavelength.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Δ W values were calculated applying Scherrer equation [ 20 ] : L=()0.89×λ/()W0.25emCos0.25emθ Δ W is the peak's halo's width at half maximum intensity. λ is X‐ray wavelength.…”
Section: Resultsmentioning
confidence: 99%
“…[ 4 ] Also, we studied the γ radiation effect on the properties of ZnS/PVA NCP. [ 20 ] The realized main phase of zinc sulfide had 4 nm common size that affects the characteristics of the NCP. In addition, the amorphous nature of the PANI‐Ag/PVA NCP was deeply enhanced owing to the γ induced interaction between the hydroxyl group of the host PVA and the NPs.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the flow behavior of the composite would increase due to the presence of ZnS, primarily associated to appreciable reduction in molecular weights of the PC [40]. In a prior work, the optical and structural properties of g irradiated ZnS/PVA NCP were investigated [41]. It is been found that the g radiation creates more compacted construction of ZnS/PVA NCP and produced good dispersion of ZnS NPs in PVA matrix.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Previously, γ radiation effects on the structural and optical properties of the developed ZnS/PVA NCP films were studied by the present authors. [16] The achieved ZnS mother phase possessed average size of 4 nm affecting, therefore, the NCP structural and optical properties. Further, the ZnS@PVA optical performance confirmed apparent well matching between the ZnS and PVA matrix.…”
Section: Introductionmentioning
confidence: 99%